A Protest Against Academic Taylorism: A New Approach to Interior Design Education - Manav, Banu; Ertürk, Zafer (ARCC Conference Repository, 2014)
The design education helps to emcompass many learning, synthesis opportunities and it has an interdisciplinary approach. However, even today, traditional educational models are developed in regard to academic taylorism, which are far away from an interdisciplinary and collaborative approach. In the present paper, we investigate the following questions; why a new approach is necessary for the structure of thinking and practice in interior design education? How can we restructure knowledge and design education in the interdisciplinary arena? Further, the paper presents a case study, discussing an educational model in interior design with a protest against "academic taylorism”. The proposed model and the educational approach has been actively used in the last six years. Some of the outcomes of the present model are; almost all students seem to be quite happy to gain an interdisciplinary view. They are also very productive since they have been working with the students in the program of cinema, painting, communication and also graphic design, this leads them to develop a common language. They also take part in national and international student competitions as a team.